Deletions and amplifications of the IGH variable and constant regions:a novel prognostic parameter in patients with multiple myeloma. (December 2020) - Rabani, Hadas; Ziv, Mira; Lavi, Noa; Aviv, Ariel; Suriu, Celia; Shalata, Adel; Haddid, Yarin; Tadmor, Tamar
Highlights: We identified two novel cytogenetic markers of poor outcome in multiple myeloma patients. Deletion in the IGH variable region was associated with worse PFS and response to treatment. Amplification of the IGH constant region was associated with worse PFS. The correlation remained valid in subgroup analysis of patients with high risk cytogenetics. Both aberrations can be detected during routine FISH analysis of MM bone marrow. Abstract: Cytogenetic abnormalities are a recognized factor in the pathogenesis of multiple myeloma (MM). While chromosomal translocations involving the IGH gene have been investigated and reported, the implications of deletions or amplifications in the IGH gene have been less frequently examined. We conducted a retrospective analysis of 260 patients with MM from Northern Israel. Fluorescent in situ hybridization (FISH) analysis of separated CD-138 positive cells was done on bone marrow samples collected between 2016 and 2018. We used IGH break apart probes to identify IGH abnormalities and performed statistical analysis of clinical and prognostic features, comparing the different cytogenetic groups. Deletions in the variable region of the IGH (IGHv) were found in 17.3 % (n = 45) of patients and correlated with significantly worse progression free survival (PFS) after two years of follow up (p = 0.008), as well as with a worse response to 1st line treatment (p = 0.037). The median PFS was 7.1 and 17.7 months in patients with and without IGHv deletion, respectively. PFS differences remained significant (p = 0.017) in subgroup analysis of patients with high-risk cytogenetics (n = 108, 19 with IGHv deletion). Overall survival was not significantly different in the two groups. Constant region (IGHc) amplifications, were less frequently found (6.15 %, n = 16), yet significantly correlated with worse PFS after two years of follow up (p = 0.023). This difference remained valid in the high-risk subgroup (p = 0.001). In Conclusion, we identified that deletion of the IGH variable region and amplification in the IGH constant region, are both associated with poor prognosis and inferior outcome in MM.